The nervous system does not compensate for an acute change in the balance of passive force between synergist muscles - Lacourpaille, L.; Nordez, A.; Hug, F. (The Journal of Experimental Biology, 2017)
It is unclear how muscle activation strategies adapt to differential acute changes in the biomechanical characteristics between synergist muscles. This issue is fundamental to understanding the control of almost every joint in the body. The aim of this human experiment was to determine whether the relative activation of the heads of the triceps surae [gastrocnemius medialis (GM), gastrocnemius lateralis (GL) and soleus (SOL)] compensates for differential changes in passive force between these muscles. Twenty-four participants performed isometric ankle plantarflexion at 20 N m and 20% of the active torque measured during a maximal contraction, at three ankle angles (30 deg of plantarflexion, 0 and 25 deg of dorsiflexion; knee fully extended). Myoelectric activity (electromyography, EMG) provided an index of neural drive. Muscle shear modulus (elastography) provided an index of muscle force. Passive dorsiflexion induced a much larger increase in passive shear modulus for GM (+657.6±257.7%) than for GL (+488.7±257.9%) and SOL (+106.6±93.0%). However, the neural drive during submaximal tasks did not compensate for this change in the balance of the passive force. Instead, when considering the contraction at 20% MVC, GL root mean square (RMS) EMG was reduced at both 0 deg (-39.4±34.5%) and 25 deg dorsiflexion (-20.6±58.6%) compared with 30 deg plantarflexion, while GM and SOL RMS EMG did not change. As a result, the GM/GL ratio of shear modulus was higher at 0 deg and 25 deg dorsiflexion than at 30 deg plantarflexion, indicating that the greater the dorsiflexion angle, the stronger the bias of force to GM compared with GL. The magnitude of this change in force balance varied greatly between participants.